PENGARUH PENGUMUMAN STOCK SPLIT TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY: Studi Kasus pada Perusahan yang Listing di BEI 2021-2022 - Mardhiyah, Muna; Nisa, Chaerani; Permana, Erwin (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
This research aims to find out the reaction of the Indonesia’s capital market to stock splits, concerning on the abnormal return and the trading volume activity as the research variables. The study population includes all publicly traded companies that have underwent stock split. The research sample is obtained through the purposive sampling techniques, comprising the publicly traded companies who underwent stock splits from 2021 to 2022. The research employs an event study method with the event window since five days before the stock split (t-5), on the event day or t0, and up to five days after the stock split (t+5), covering a total of 11 trading days. The Wilcoxon Signed Rank test is used for testing the hypothesis. The research indicates there is a significant decrease in abnormal return after the announcement of the stock split. However, there is no significant difference in the trading volume activity following this event.